Loss of CIB2 Causes Profound Hearing Loss and Abolishes Mechanoelectrical Transduction in Mice - Wang, Yanfei; Li, Jie; Yao, Xuerui; Li, Wei; Du, Haibo; Tang, Mingliang; Xiong, Wei; Chai, Renjie; Xu, Zhigang (Frontiers in Molecular Neuroscience, 2017)
CIB2 belongs to a protein family with four known members, CIB1 through CIB4, which are characterized by multiple calcium-binding EF-hand domains. Among the family members, the Cib1 and Cib2 genes are expressed in mouse cochlear hair cells, and mutations in the human CIB2 gene have been associated with nonsyndromic deafness DFNB48 and syndromic deafness USH1J. To further explore the function of CIB1 and CIB2 in hearing, we established Cib1 and Cib2 knockout mice using the clustered regularly interspaced short palindromic repeat (CRISPR)-associated Cas9 nuclease (CRISPR/Cas9) genome editing technique. We found that loss of CIB1 protein does not affect auditory function, whereas loss of CIB2 protein causes profound hearing loss in mice. Further investigation revealed that hair cell stereocilia development is affected in Cib2 knockout mice. Noticeably, loss of CIB2 abolishes mechanoelectrical transduction currents in auditory hair cells. In conclusion, we show here that although both CIB1 and CIB2 are readily detected in the cochlea, only loss of CIB2 results in profound hearing loss, and that CIB2 is essential for auditory hair cell mechanoelectrical transduction.